Randomized control trial to test the effect of a feed additive on Campylobacter contamination in commercial broiler flocks up to slaughter. (4th February 2018) - Huneau‐Salaün, A.; Guyard‐Nicodème, M.; Benzoni, G.; Gautier, X.; Quesne, S.; Poëzevara, T.; Chemaly, M.
Summary: A randomized controlled trial (RCT) was carried to evaluate the effect of a feed additive on Campylobacter contamination of broilers reared in commercial conditions. Twenty‐four broiler flocks naturally contaminated with Campylobacter were enrolled in the RCT: 12 were assigned to a control group (C) fed with a conventional finishing feed from 4 weeks of age to slaughter (around 35 days), and the other group of 12 flocks (S) was fed with a finishing feed supplemented with 250 ppm of a patented feed additive (an ion‐exchanged clay compound) previously proven to reduce Campylobacter contamination in broiler caeca under experimental conditions. Enumeration of Campylobacter colonies in caeca (8 per flock) was carried out following ISO standards before feed distribution and at slaughter. Before treatment, the caecal Campylobacter load tended to be lower in C flocks (7.1 ± 1.9 log CFU/g, CI95% [6.6–7.5]) than in S flocks (7.7 ± 1.0 log UFC/g, CI95% [7.5–7.9]) ( p = .05). At slaughter, the bacterial load was similar in the S (7.7 ± 1.0 log CFU/g, CI95% [7.5–7.9]) and C groups (7.5 ± 1.2 log CFU/g, CI95% [7.2–7.8]) ( p = .73). Therefore, the feed additive had no significant effect on the caecal Campylobacter load at slaughter under the tested conditions. The logistical constraints inherent in field trials and the natural variability of Campylobacter contamination in naturally infected broiler flocks make it difficult to reproduce experimental results in in situ farm conditions. RCT testing of an intervention strategy in commercial situation is therefore a key step in evaluating pre‐harvest interventions against food‐borne pathogens.